2009
DOI: 10.1152/physiolgenomics.90301.2008
|View full text |Cite
|
Sign up to set email alerts
|

Expression of genes involved in GABAergic neurotransmission in anoxic crucian carp brain (Carassius carassius)

Abstract: Ellefsen S, Stensløkken K, Fagernes CE, Kristensen TA, Nilsson GE. Expression of genes involved in GABAergic neurotransmission in anoxic crucian carp brain (Carassius carassius). Physiol Genomics 36: 61-68, 2009. First published October 28, 2008 doi:10.1152/physiolgenomics.90301.2008.-The crucian carp, Carassius carassius, survives days to months without oxygen, depending on temperature. In the anoxic crucian carp brain, increased GABAergic inhibition, mediated by increased extracellular levels of GABA, has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 44 publications
(64 reference statements)
1
29
0
Order By: Relevance
“…Compared with levels in turtle brain, the anoxia-mediated increase in extracellular [GABA] in crucian carp brain is quite modest and doubles after 5 h of anoxia (Hylland and Nilsson, 1999). Furthermore, with anoxia, GABA removal from the extracellular space is significantly reduced because the expression of GABA transporter proteins decreases by 80%, increasing the effective extracellular [GABA] further (Ellefsen et al, 2009). We observed a significant increase in neuronal V m with anoxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with levels in turtle brain, the anoxia-mediated increase in extracellular [GABA] in crucian carp brain is quite modest and doubles after 5 h of anoxia (Hylland and Nilsson, 1999). Furthermore, with anoxia, GABA removal from the extracellular space is significantly reduced because the expression of GABA transporter proteins decreases by 80%, increasing the effective extracellular [GABA] further (Ellefsen et al, 2009). We observed a significant increase in neuronal V m with anoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Cl − flow occurs through both synaptic ( phasic) and extrasynaptic (tonic) GABA receptors (Blaesse et al, 2009). Localization of GABA A receptors has not been investigated in goldfish neurons; however, crucian carp neurons express the gamma subunit, which is necessary for phasic currents, and delta subunits, which in mammalian brain are extrasynaptic (Mody, 2001;Ellefsen et al, 2009). By applying GZ, we likely inhibited the activity of phasic currents as GZ has a greater affinity for synaptic GABA A receptors (Mody, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there is a slight fall in mRNA levels of GABA A -receptor subunits in crucian carp exposed to 1-7 d of anoxia at 8ЊC, suggesting a more modest and modulated GABAergic inhibition in this species (Ellefsen et al 2009). Nevertheless, pharmacological inhibition of GABA receptors or GABA synthesis causes a threefold increase in ethanol release to the water by anoxic crucian carp, suggesting a significant GABAergic component in anoxic whole-body metabolic depression (Nilsson 1992).…”
Section: Acute Metabolic Depression In Anoxia-tolerant Brainmentioning
confidence: 95%
“…However, two contributing mechanisms have been suggested. A study has shown that the mRNA levels of transporter proteins of the GAT2 family, which is responsible for a major part of GABA reuptake, fall by ∼75% during anoxia (Ellefsen et al 2009). Thus, there may be a transcriptionally induced suppression of GABA reuptake from the extracellular space during anoxia.…”
Section: Acute Metabolic Depression In Anoxia-tolerant Brainmentioning
confidence: 99%
“…Oddly, turtles appear to maintain vision during anoxia (Stensløkken et al 2008b). A moderate increase in extracellular GABA levels (Hylland and Nilsson 1999), possibly mediated by a reduced expression of GABA reuptake proteins (Ellefsen et al 2009), is probably involved in depressing energy use in the crucian carp (Nilsson 1992), but only to a level that is compatible with some physical activity. Other mechanisms that may be involved in defending brain and heart energy charge in crucian carp include phosphorylation of AMPactivated kinase that in turn will initiate mechanisms that increase energy supply and reduce energy use (Stensløkken et al 2008a).…”
Section: Strategies Of Anoxia Tolerance In Ectothermic Vertebratesmentioning
confidence: 99%